Respon Pertumbuhan, Produksi Dan Persentase Serangan Penyakit Pada Tanaman Bawang Merah (Allium Ascalonicum L.) Yang Di Beri 3 Jenis Kompos Kulit Buah Dan Poc Kubis - Roy Fernando; Asmah Indrawati; Azwana Azwana (Jurnal Ilmiah Pertanian ( JIPERTA), 2020)
Onion is one of predominant flavor in Indonesia culinary which its quantity should be increased contantly. The aim of research was to invesitigate the respond of onion growth toward the treatment combination between POC cabbage and Tree types of fruit skin. This research was performed in a Factorial Randomized Block Design (RBD), which consists of 2 treatment factors, namely: 1) compost 2) liquid organic fertilizer of cabbage waste. The parameters observed in this study were plant height, number of leaves, number of tubers per sample plant, production per sample, production per plot and percentage of plant disease attack. As for the results obtained from this study, namely: 1) Giving various types of fruit skin compost did not significantly affect height, number of leaves, number of tubers, production per sample plant and production per plot of onion plants; 2) liquid organic fertilizer cabbage application has no significant effect on height, number of leaves, number of tubers and production per sample plant, but has a significant effect on production per plot of onion plant; and 3) Combination between the fruits compost and the liquid organic fertilizer that is not real influence on the plant height, the number of leaves, the number of bulbs and production per crop samples, but the effect is very real towards production per plot of the anion plants